2003
DOI: 10.5194/aab-46-63-2003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on associations between leptin gene (<i>LEP</i>) and some reproduction performance traits of boars

Abstract: SummaryStudies on porcine genome contributed to identification of polymorphic loci of the genes that may influence the level of reproduction-related traits. The LEP gene codes for leptin -a protein secreted to blood from adipocytes, important for food intake, energy expenditure, and immune response; the protein also influences some functions of mammalian reproductive system. The aim of this study was to determine the polymorphism of HinfI in the leptin gene and its effect on selected qualitative and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…In younger time studies on porcine genome contributed to identification of polymorphic loci of the genes that may influence the level reproduction-relates traits in sows (KMIEĆ, et al, 2001;LINVILLE, et al, 2001;DRÖGEMÜLLER et al, 1999) and boars (MAĆKOWSKI, et al, 2004;KMIEĆ et al, 2003;SCHLINGMANN et al, 2002;KMIEĆ et al, 2001). Progress in genetics and molecular techniques has enabled application of DNA polymorphism by selection of animals known as marker-assisted selection (MAS).…”
Section: Introductionmentioning
confidence: 99%
“…In younger time studies on porcine genome contributed to identification of polymorphic loci of the genes that may influence the level reproduction-relates traits in sows (KMIEĆ, et al, 2001;LINVILLE, et al, 2001;DRÖGEMÜLLER et al, 1999) and boars (MAĆKOWSKI, et al, 2004;KMIEĆ et al, 2003;SCHLINGMANN et al, 2002;KMIEĆ et al, 2001). Progress in genetics and molecular techniques has enabled application of DNA polymorphism by selection of animals known as marker-assisted selection (MAS).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hasanain et al (2017) and Dalvi et al (2018) reported non-significant (P<0.05) association of sperm concentration with prolactin and FSH beta gene, respectively. However, Kmieć et al (2003) reported a significant (P<0.05) predominance of LEP CT and TT genotypic boars in respect to sperm concentration in their ejaculates.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, results of the semen quality parameters in buffalo bulls revealed non-significant (P>0.05) correlation between leptin gene polymorphism and ejaculatory volume. Kmieć et al (2003) investigated the effect of HinfI polymorphism of leptin gene and reported a significant (P<0.05) predominance of LEP CT and TT genotypic boars in respect to ejaculatory volume. However, association of FSH beta gene and prolactin gene polymorphism with semen volume was non-significant (Ghasemi and Ghorbani, 2014;Hasanain et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlüsselwörter: Steroid-21-Hydroxylase-Gene, Schwein, Wurfgröße, Reproduktion, Polymorphismus Introduction Last years the identification of genes or markers associated with reproductive traits in swine is an important area of research (DROEGEMUELLER et al, 1999;KMIEĆ et al, 2001;SCHLINGMANN et al, 2002;KMIEĆ et al, 2003;MAĆKOWSKI et al, 2004;SCHWARZ et al, 2005) because the large economic impact these discoveries could have on the swine industry. One of the most important enzymatic complexes that take part in the synthesis of adrenal steroids is 21-hydroxylase (CYP21).…”
Section: Zusammenfassungmentioning
confidence: 99%